Sales Growth and Firm Size Impact on Firm Value with ROA as a Moderating Variable - Thomas Sumarsan Goh; Henry Henry; Erika Erika; Albert Albert (Universitas Mercu Buana, 2022)
Objectives: This study aims to determine the sales growth and firm size impact of the firm value, and the return on assets as the moderating variable. These independent variables are the sales growth and firm size, where the dependent variable is firm value. The objects of this study are the consumer goods companies which was listed on the Indonesia Stock Exchange market from 2015 to 2020.Methodology: The amount of sample is ten consumer goods companies based on the purposive sampling technique. The research method is using SPSS application to run the regression analysis and which covered the descriptive statistics, classical assumption tests, multiple linear regression analysis, moderation regression analysis, and the hypotheses tests. The data of the study are normally distributed, free from multicollinearity and heteroscedasticity.Finding: The hypothesis results show that sales growth results have negative impact and not significant to the firm value; the total assets have positive impact and not significant on the firm value; sales growth and total assets have impact on the firm value which is not significant simultaneously. Investors have to be careful on investing in the company because if they are taking sales growth and firm size into the account to invest, this may make mistakes. The variable of ROA also cannot moderate the model. Conclusion: A company with high sales growth and large firm size does not guarantee to operate efficiently to generate profit and increase the firm value.